Concrete Representational Abstract Number Boards Optimize Slow Learner Statistical Data Mastery: Papan Bilangan Konkret Representasional Abstrak Mengoptimalkan Penguasaan Data Statistik Siswa Lamban - Akhmad Fauzan Habibie; Rendy Roos Handoyo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Inclusive secondary mathematics education requires adaptive instructional strategies accommodating diverse cognitive profiles. Specific Background Students at risk of slow learning often struggle with abstract concepts like measures of central tendency due to underlying arithmetic deficits in addition and division. Knowledge Gap Traditional instruction predominantly utilizes two-dimensional representations and symbolic calculations, failing to provide the transitional physical manipulatives necessary to reduce cognitive load for borderline learners. Aims This Classroom Action Research investigates the application of an integrated manipulative medium to optimize mode, median, and mean comprehension among eighth-grade students in a disadvantaged region. Results Following two pedagogical cycles, classical learning mastery elevated from 33 percent to 86 percent. Specifically for the twelve borderline participants, average scores progressed from a baseline of 32.50 to 65.83, with classical mastery jumping from zero to 75 percent. Observational data confirmed increased participation across tangible, visual, and symbolic mathematical stages. Novelty This study distinctly integrates physical unit manipulatives into a sequenced visual framework, offering a uniquely structured transition from tangible sorting to symbolic arithmetic specifically tailored for borderline intellectual capacities. Implications Educational practitioners must integrate sequenced manipulative media when introducing complex mathematical procedures to ensure inclusive conceptual development. Highlights Sequenced physical manipulatives significantly elevate mathematical comprehension among marginalized eighth-grade cohorts. Average procedural performance metrics for borderline participants jumped from zero to seventy-five percent after two pedagogical cycles. Structured tangible-to-symbolic transitions effectively reduce cognitive load during addition and division arithmetic tasks. Keywords Inclusive Education; Mathematics Instruction; Tangible Manipulatives; Central Tendency; Cognitive Load